Impoliteness in Jeremy Clarkson’s humor in the tv series Top Gear - Elkholy Elkholy; Nizam Ahsani (NOTION: Journal of Linguistics, Literature, and Culture, 2023)
This research was conducted  to observe impoliteness strategies employed by Jeremy Clarkson in his humor in the TV Series Top Gear with the intention to unveil which strategy he utilized most and elucidate the reason upon the most and least occurring impoliteness strategies. The present research utilizes Culpeper’s (1996) model of impoliteness super strategies as the main framework to identify, analyze, and elaborate the research data. Other theories related to impoliteness such as face-threatening act and politeness was also utilized to assist the analysis process. The result of the research revealed that negative impoliteness strategy was the most commonly used strategy through which Jeremy Clarkson delivers his humor. Contrary to the withhold politeness strategy which accounted for the least occurring strategy. The explanation upon the result to be the way they are could be referred back to Jeremy Clarkson’s main intentions of uttering impolite remarks—in an effort to amuse the audience and keep the show entertaining.